PENINGKATAN MUTU MINYAK BATUBARA DENGAN PROSES HIDROKATALITIK - Ade Syafrinaldi; Dhani Avianto Sugeng (Jurnal Energi dan Lingkungan (Enerlink), 2007)
The result of hydrotreating coal derived oil was investigated. Compared to crudepetroleum oil, oil produced from liquefaction of coal, the coal liquid needs afurther treatment before being used as same grade of petroleum products. Thestorage stability and most important the quality of the coal liquid oil are the mostcritical factors for this matter. The concentrations of nitrogen, sulfur, oxygen andaromatic hydrocarbon are way much too high for the coal oil to be directlyconverted into synthetic fuel like gasoline, kerosene or gas oil. In a brown coalliquefaction plant, this special unit is integrally designed with the whole plant, wellknown as the inline hydro-treatment unit, which has two process stages , the firsthydro-treatment and the second hydro-treatment. This paper will discuss thecharacteristic of the hydro-treated coal liquid oil concerning its storage stabilityand quality.Kata kunci: coal liquefaction, storage stability, quality, coal liquid oil, inlinehydro-treatment, dry sludge